The decline of malaria in Vietnam, 1991-2014 - Goldlust, S; Thuan, P; Giang, D; Thang, N; Thwaites, G; Farrar, J; Thanh, N; Nguyen, T; Grenfell, B; Boni, M; Hien, T (BioMed Central, 2018)
Background Despite the well-documented clinical efficacy of artemisinin-based combination therapy (ACT) against malaria, the population-level effects of ACT have not been studied thoroughly until recently. An ideal case study for these population-level effects can be found in Vietnam’s gradual adoption of artemisinin in the 1990s. Methods and results Analysis of Vietnam’s national annual malaria reports (1991–2014) revealed that a 10% increase in artemisinin procurement corresponded to a 32.8% (95% CI 27.7–37.5%) decline in estimated malaria cases. There was no consistent national or regional effect of vector control on malaria. The association between urbanization and malaria was generally negative and sometimes statistically significant. Conclusions The decline of malaria in Vietnam can largely be attributed to the adoption of artemisinin-based case management. Recent analyses from Africa showed that insecticide-treated nets had the greatest effect on lowering malaria prevalence, suggesting that the success of interventions is region-specific. Continuing malaria elimination efforts should focus on both vector control and increased access to ACT.